2018
DOI: 10.1038/s41598-017-17350-w
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between spectrotemporal modulation detection and music perception in normal-hearing, hearing-impaired, and cochlear implant listeners

Abstract: The objective of this study was to examine the relationship between spectrotemporal modulation (STM) sensitivity and the ability to perceive music. Ten normal-nearing (NH) listeners, ten hearing aid (HA) users with moderate hearing loss, and ten cochlear Implant (CI) users participated in this study. Three different types of psychoacoustic tests including spectral modulation detection (SMD), temporal modulation detection (TMD), and STM were administered. Performances on these psychoacoustic tests were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Although some studies in CI users have found a correlation between measures of spectral resolution (e.g., spectral-ripple discrimination or spatial tuning curves) and speech perception in quiet (Anderson et al , 2011; Henry and Turner, 2003; Henry et al , 2005) and in noise (Gifford et al , 2018; Won et al , 2007), others have not (Anderson et al , 2012). These apparent discrepancies may be in part because most measures of spectral resolution, such as spectral-ripple detection (Anderson et al , 2012; Gifford et al , 2018), spectral-ripple discrimination (Anderson et al , 2011; Anderson et al , 2012; Henry and Turner, 2003; Henry et al , 2005; Won et al , 2007), and spectrotemporal-modulation detection (Aronoff and Landsberger, 2013; Choi et al , 2018; Won et al , 2015), use broadband stimuli, but can be performed using only a limited portion of the entire spectrum (e.g., Anderson et al , 2011). In contrast, speech perception benefits from information across the entire spectrum, meaning that good spectral resolution at just one cochlear location will not be sufficient to provide good intelligibility.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies in CI users have found a correlation between measures of spectral resolution (e.g., spectral-ripple discrimination or spatial tuning curves) and speech perception in quiet (Anderson et al , 2011; Henry and Turner, 2003; Henry et al , 2005) and in noise (Gifford et al , 2018; Won et al , 2007), others have not (Anderson et al , 2012). These apparent discrepancies may be in part because most measures of spectral resolution, such as spectral-ripple detection (Anderson et al , 2012; Gifford et al , 2018), spectral-ripple discrimination (Anderson et al , 2011; Anderson et al , 2012; Henry and Turner, 2003; Henry et al , 2005; Won et al , 2007), and spectrotemporal-modulation detection (Aronoff and Landsberger, 2013; Choi et al , 2018; Won et al , 2015), use broadband stimuli, but can be performed using only a limited portion of the entire spectrum (e.g., Anderson et al , 2011). In contrast, speech perception benefits from information across the entire spectrum, meaning that good spectral resolution at just one cochlear location will not be sufficient to provide good intelligibility.…”
Section: Introductionmentioning
confidence: 99%
“…Heng et al (2011) and Kong et al (2011) both evaluated the relationship between timbre perception and temporal sensitivity in CI recipients and both studies emphasized the importance of temporal sensitivity in the perception of timbre. Recently Choi et al (2018) evaluated the spectrotemporal modulation sensitivity and music perception of normal hearing listeners, hearing aid users, and CI recipients, and there was a significant correlation between music perception abilities and spectrotemporal modulation sensitivity, but there was no correlation between music perception and spectral or temporal modulation sensitivities alone. Golub et al (2012) compared Hybrid CI recipients with standard CI recipients and pitch perception and spectral ripple discrimination (SRD) performance were significantly better in the Hybrid group and there was no advantage of residual acoustic hearing for temporal sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…If one assumes that polyphonic music tends to play with, not against, the principles of auditory scene analysis in order to be apprehensible, a pertinent question becomes whether potentially hearing-impaired and older listeners can still participate in this sort of play. In fact, despite decades of substantial work on hearing impairment and speech, research on music perception has only started to address the effects of mild to moderate forms of hearing impairment on music listening (Madsen and Moore, 2014;Kirchberger and Russo, 2015;Choi et al, 2018); for research on cochlear implant listeners, see McDermott (2011), Marozeau et al (2013), and Marozeau and Lamping (2019). Regarding the role of age in auditory scene analysis, Zendel and Alain (2013) found that younger musicians showed a greater tendency to segregate concurrent sounds compared to younger musicians and older musicians and non-musicians.…”
Section: Introductionmentioning
confidence: 99%